Factors Affecting Virtual Team Performance in UAE Organisations - Abdulla Al Kaabi, Hamad Mohammed; Sidek, Safiah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
The concept of the virtual teams is getting popularized all over the world to connect different skilled professional on a single forum to achieve a common goal. To get maximum of the benefits of the virtual teams, it is essential to understand the associate problems and the factors which affect the virtual team performance. This paper uncovered several factors in the major domains of the communication competency, cultural intelligence, and knowledge sharing and collaboration parameters affecting virtual team performance in UAE. Collection of the data focused on recording the perception of the MNC employees in UAE where 318 valid data samples were gathered and analyzed for Mean value and standard deviation. The analysis results revealed that all the parameters have high level relation with virtual team performance. These finding can be helpful for preparing effective strategies to improve the communication system and maximize the performance of the virtual teams.